Employment in the cultural sector in 2005 - Eric Cléron
The annual National Institute for Statistics and Economic Studies (Institut national de la statistique et des études économiques, or INSEE Employment Survey, which is carried out each year by the Département des études, de la prospective et des statistiques (DEPS), allows the overall economic weight of jobs in the cultural sector to be measured, of which over half are now based in the cultural industries.